Levosalbutamol and new opportunities for the treatment of bronchial asthma (review of the related studies) - A. A. Lidzhieva; E. A. Smolyarchuk (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The review describes the new chirally pure drug - levosalbutamol for the treatment of bronchial asthma. It summarizes historical information about the development of the product, data on its pharmacological properties and the results of clinical trials conducted in healthy volunteers and in patients. The presented data allow to draw conclusions on the drug pharmacokinetic properties, its efficacy and safety in patients suffering from bronchial asthma.